Trapping intermediate MLCT states in low-symmetry {Ru(bpy)} complexes. Issue 11 (19th September 2017) - Cadranel, Alejandro; Oviedo, Paola S.; Pieslinger, German E.; Yamazaki, Shiori; Kleiman, Valeria D.; Baraldo, Luis M.; Guldi, Dirk M.
Abstract : The picosecond excited state dynamics of [Ru(tpm)(bpy)(NCS)] + (RubNCS + ) and [Ru(tpm)(bpy)(CN)] + (RubCN + ) (tpm = tris(1-pyrazolyl)methane, bpy = 2, 2′-bipyridine) reveal an intermediate MLCT excited state living in the 300 ps timescale. Abstract : The picosecond excited state dynamics of [Ru(tpm)(bpy)(NCS)] + (RubNCS + ) and [Ru(tpm)(bpy)(CN)] + (RubCN + ) (tpm = tris(1-pyrazolyl)methane, bpy = 2, 2′-bipyridine) have been analyzed by means of transient absorption measurements and spectroelectrochemistry. Emissive 3 MLCTs with (GS)HOMO(h + )–(GS)LUMO(e − ) configurations are the lowest triplet excited states regardless of whether 387 or 505 nm photoexcitation is used. 387 nm photoexcitation yields, after a few picoseconds, the emissive 3 MLCTs. In contrast, 505 nm photoexcitation populates an intermediate excited state that we assign as a 3 MLCT state, in which the hole sits in a metal-centered orbital of different symmetry, prior to its conversion to the emissive 3 MLCTs. The disparities in terms of electronic configuration between the intermediate and the emissive 3 MLCTs have two important consequences. On one hand, both states feature very different fingerprint absorptions in transient absorption measurements. On the other hand, the reconfiguration is impeded by a kinetic barrier. As such, the conversion is followed spectroscopically and kinetically on the 300 ps timescale.